Survey of Sports Facilities and Infrastructure in Supporting Physical Education Learning at SMA Negeri 1 Nogosari - Herta Lofty Mustikayanti; Gatot Jariono (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the condition of physical education facilities and infrastructure in SMA Negeri 1 Nogosari. The subjects in this study were students of SMA Negeri 1 Nogosari who collected 75 students. The data analysis of this research used quantitative descriptive analysis. The research technique used is a questionnaire. Data collection techniques with observation, data validity using Validity and Reliability Test, while the results of this study are based on the results of percentage descriptive analysis. Physical education facilities and infrastructure is one of the elements supporting the success of learning. Facilities are not important to support success and can be interpreted as a set of tools used for the learning process. Infrastructure is the same as means, which are equally important in supporting the success of an activity. Quality learning relies heavily on teacher creativity, learning that has high motivation can achieve success in achieving learning targets effectively and efficiently. The infrastructure factor can be assessed as good at 48.47%. However, it is necessary to conduct further research related to students' interest and motivation in learning about physical education.